Oral anticoagulant therapy and outcome in patients with stroke. A retrospective nation‐wide cohort study in Austria 2012–2017. Issue 10 (3rd June 2021) - Preinreich, Jasmina; Sheikh Rezaei, Safoura; Mittlböck, Martina; Greisenegger, Stefan; Reichardt, Berthold; Wolzt, Michael
Abstract: Purpose: Patients with stroke are at high risk of recurrence of vascular events. Non‐vitamin K oral anticoagulant (NOAC) and vitamin K antagonists (VKA) are used as secondary prophylaxis. The aim of this study was to evaluate the utilization of NOAC and VKA, and their impact on re‐stroke or death in Austria. Methods: We analyzed retrospective data between 2012 and 2017 from medical services covered by the health insurance funds, which provides health care for all residents in Austria. Patients without anticoagulant medication 3 months preceding the index event were eligible. Results: 76 354 patients were discharged with a hospital diagnosis of stroke. From these, 16 436 patients with a median age of 78 years received VKA or NOAC. After adjustment, the recurrence of stroke was less frequent in patients with NOAC compared to those with VKA (HR 0.87; 95%CI 0.77–0.97). However, there was no difference in mortality rate after adjustment for age, sex, and co‐morbidities for patients with NOAC (HR 1.0; 95%CI 0.92–1.08). Diabetes (HR 1.25, 95%CI 1.08–1.45; HR 1.25, 95% CI 1.13–1.38) and cardiovascular disease (HR 1.43, 95%CI 1.24–1.65; HR 1.27, 95%CI 1.16–1.39) were significantly associated with re‐stroke or death. Younger age ( p = 0.0028; HR 0.99, 95%CI 0.99–0.99) was significantly associated with re‐stroke, and advanced age ( p < 0.0001; HR 1.09, 95%CI 1.08–1.09) with death. Conclusion: NOAC prescription is related with a reduced risk of re‐stroke but increased mortality compared to patients with VKA. The event risk is associated with diabetes, cardiovascular disease and age.